Young people and social change : individualization and risk in late modernity - Furlong, Andy.; Cartmel, Fred. (Buckingham [England] ; Philadelphia : Open University Press, 1997)
The risk society. Change and cotinuity in education. Social change and labour market transitions. Changing patterns of dependency. Leisure and lifestyles. Health risks in late modernity. Crime and insecurity. Politics and participation. The epistemological fallacy of late modernity.
Keywords: Great Britain; Social conditions; Youth; Youth -- Great Britain -- Social conditions; Great Britain -- Social conditions -- 1945-